Rare Ectopic Pregnancies – A Literature Review for the Period 2007 – 2019 on Locations Outside the Uterus and Fallopian Tubes - Eisner, Sophie M.; Ebert, Andreas D.; David, Matthias (Geburtshilfe und Frauenheilkunde, 2020)
The majority of ectopic pregnancies (EP) are tubal pregnancies, but other implantation sites outside the uterus and tubes are also found. These rare EP locations present a particular diagnostic and therapeutic challenge. We present an overview of potential very rare locations of ectopic pregnancies, their symptoms, diagnosis and treatment, based on a systematic analysis of case reports. A literature review of the databases PubMed, Livivo and Google Scholar for the period 2007 to 2019 was carried out. A total of 113 publications were included in our review. These studies describe EP implantations in the posterior cul-de-sac, on the uterine serosa and uterine ligaments, in the vicinity of almost all intraperitoneal organs, on the abdominal wall as well as in retroperitoneal sites. The most common presenting symptom was abdominal pain occurring in different locations. The diagnostic procedures included various imaging procedures and/or explorative surgery at different advanced stages of pregnancy. The most common and preferred option was laparotomy for surgical treatment. The placenta was successfully resected in the majority of cases. A rare EP location should be considered when making a differential diagnosis in patients of child-bearing age with abdominal pain.Das Gros extrauteriner Schwangerschaften (EUG) sind Tubargraviditäten, doch auch andere Implantationsstellen außerhalb des Uterus und der Adnexe kommen vor. Diese seltenen Lokalisationen einer EUG stellen eine besondere diagnostische und therapeutische Herausforderung dar. Anhand einer systematischen Analyse von Fallberichten wird eine Übersicht zu möglichen sehr seltenen Lokalisationen ektoper Schwangerschaften, deren Symptomatik, Diagnostik und Therapie gegeben. Dazu wurde eine Literaturrecherche in den Datenbanken PubMed, Livivo und Google Scholar für den Zeitraum 2007 bis 2019 durchgeführt. Insgesamt wurden 113 Publikationen eingeschlossen. Diese Studien beschrieben EUG-Implantationen im Douglas-Raum, an der Uterusserosa und dem uterinen Bandapparat, im Bereich nahezu aller intraperitonealer Organe, der Bauchwand sowie retroperitoneale Lokalisationen. Das häufigste Symptom war der variabel lokalisierte abdominale Schmerz. Die diagnostischen Maßnahmen umfassten unterschiedliche Bildgebungsverfahren und/oder explorative Operationen in verschieden weit fortgeschrittenem Schwangerschaftsalter. Als häufigste Therapieoption wurde die operative Befundsanierung per laparotomiam gewählt. Die Plazenta konnte in der Mehrheit der Fälle erfolgreich reseziert werden. Eine EUG seltener Lokalisation sollte als mögliche Differenzialdiagnose bei Patientinnen im reproduktionsfähigen Alter mit abdominellen Beschwerden bedacht werden.
Keywords: ectopic pregnancy; rare locations; abdominal pregnancy